Análise do impacto de sistemas fotovoltaicos conectados à rede de distribuição na qualidade da energia de uma smart city: Análise do impacto de sistemas fotovoltaicos conectados à rede de distribuição na qualidade da energia de uma smart city - Falcão, Mariana Costa [UNESP] (2015)
This paper presents analysis of the impact of PV systems connected to the distribution network in the electric power quality in three consumers in a city where is launching a Smart City project. It is used as a reference for the analysis the module 8 of Distribution Procedures (PRODIST). The analyzes are of great importance to have an evaluation of how the consumers power quality will be affected when PV systems are connected to their homes, their businesses or even to their industries. The concepts presented in the literature were used for the understanding subjects such as Smart Cities, Smart Grid and power quality problems. The results of power quality measurements are analyzed from a comparison of estimated coefficients before and after the installation of photovoltaic systems on consumers. By observing the differences between the results it was possible to conclude which the impacts were caused by the presence of the source of distributed generation in question